Innovación de un software educativo interactivo como refuerzo didáctico para el interaprendizaje de la asignatura de matemáticas aplicada a la educación en la unidad educativa león Febres Cordero parroquia San Juan cantón Pueblo viejo Provincia los Ríos - Ilbay Zatan, Narcisa Rosario (2016)
This paper aims to analyze the Didáctico Inter-Learning that has developed Interactive Software which apply teachers in the teaching-learning process in the area of mathematics, students of the Education Unit León Febres Cordero parish San Juan of Canton Pueblo Viejo province of Los Rios., come to discover all sales and disadvantages that may occur in the use of educational software used by teachers in this school, which will serve as a base element for making suggestions and recommendations at the end Graduation of this work. The first chapter presents the research topic, the contextual framework, the difficult situation, the research problem and serve as reference for carrying out the work with students during the school year 2016. The second chapter presents the delimitation of research , history, objectives, all the theoretical foundation with which teaching and learning processes are managed, same that maintain a medium level of educational quality, and do not allow the consensual implementation of methodological parameters for a comprehensive and meaningful development the students. The third chapter is concerned with analysis and interpretation of results, including the organization of results statistically with their percentages, relevant conclusions and recommendations, according to the statistical analysis of research data. This paper ends with the reference materials.